Respuestas
Respuesta dada por:
2
OJO:
a/b ÷ c/d = (a*d)/ (b*c)
De tal modo:
[ (1/2) / (3/4)] / ( 3/2 ) = [ (1*4)/(2/3) ] / (3/2)
[ (1/2) / (3/4)] / ( 3/2 ) = [ 2/3] / (3/2)
[ (1/2) / (3/4)] / ( 3/2 ) = (2*2)/(3*3)
[ (1/2) / (3/4)] / ( 3/2 ) = 4/9 ← Respuesta
Eso es todo!!
a/b ÷ c/d = (a*d)/ (b*c)
De tal modo:
[ (1/2) / (3/4)] / ( 3/2 ) = [ (1*4)/(2/3) ] / (3/2)
[ (1/2) / (3/4)] / ( 3/2 ) = [ 2/3] / (3/2)
[ (1/2) / (3/4)] / ( 3/2 ) = (2*2)/(3*3)
[ (1/2) / (3/4)] / ( 3/2 ) = 4/9 ← Respuesta
Eso es todo!!
Respuesta dada por:
1
(1/2 / 3/4) / 3/2
primero resolvemos el parentesis asi:
(
)
multiplicamos
![\frac{\frac{4}{6} }{ \frac{3}{2} } \frac{\frac{4}{6} }{ \frac{3}{2} }](https://tex.z-dn.net/?f=+%5Cfrac%7B%5Cfrac%7B4%7D%7B6%7D+%7D%7B+%5Cfrac%7B3%7D%7B2%7D+%7D++)
resolvemos la fraccion
![\frac{4}{6} * \frac{2}{3} \frac{4}{6} * \frac{2}{3}](https://tex.z-dn.net/?f=+%5Cfrac%7B4%7D%7B6%7D+%2A+%5Cfrac%7B2%7D%7B3%7D+)
multiplicamos
![\frac{8}{18} \frac{8}{18}](https://tex.z-dn.net/?f=+%5Cfrac%7B8%7D%7B18%7D+)
simplificamos
![\frac{4}{9} \frac{4}{9}](https://tex.z-dn.net/?f=+%5Cfrac%7B4%7D%7B9%7D+)
:)
primero resolvemos el parentesis asi:
(
multiplicamos
resolvemos la fraccion
multiplicamos
simplificamos
:)
Preguntas similares
hace 7 años
hace 7 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años